Functional Outcome of Intra-articular Fractures of Distal Radius: ORIF with Locking Plate vs CRPP - Shrestha, Bhola; Sapkota, K; Kandel, IS; Dhakal, RM; Bista, K (Journal of Gandaki Medical College-Nepal, 2018)
Background: Distal radius fractures are common, costly, and increasing in incidence. Closed reduction and percutaneous K wires fixation and ORIF with locking plate fixation are two of the mostly used surgical treatments for dorsally displaced distal radius fractures. However, there is uncertainty which of these treatments is superior.Methods: This is a prospective study on 40 patients. Twenty patients had closed reduction and percutaneous pinning (CRPP) with K wires (Group A) and 20 patients had open reduction and internal fixation (ORIF) with locking plate and screws (Group B). Evaluation were done in the means of DASH scores and ROM of operated wrist on 1.5 months, three months and six months follow up period.Results: Though the overall functional outcome is comparatively better with Group B, the significant difference for most variables like DASH Scores, extension, supination and ulnar deviation were found at early part of treatment only. The flexion and radial deviation bear no significant outcomes at all intervals of evaluations. Superficial wound infection was more common in patients treated with K-wires but otherwise no difference in complication rates was noted.Conclusion: Locking plate fixation provided lower DASH scores and reduced total postoperative complications compared to CRPP group over six months follow-up period. However, these differences were significant in early part of treatment. Further research is required to better delineate the confirmation.